Clinical and In Vitro Safety of Heyndrickxia coagulans AO 1167B: A Double-Blind, Placebo-Controlled Trial - Gissel García; Josanne Soto; Antonio Díaz; Jesús Barreto; Carmen Soto; Ana Beatriz Pérez; Suselys Boffill; Ángela Gutiérrez; Raúl de Jesús Cano (Microorganisms, 2024)
(1) Background: Heyndrickxia coagulans, a lactic acid-producing bacterium, displays characteristics of both Lactobacillus and Bacillus genera. Clinical evidence suggests its potential health benefits. This study evaluated the safety of H. coagulans AO1167B as a candidate probiotic supplement. (2) Methods: Strain identification was confirmed through morphological, cultural, and genomic analyses, including 16S RNA and whole genome sequencing to assess antimicrobial resistance and virulence factors. Phenotypic tests, such as disk diffusion for antimicrobial resistance, and safety assays for cytotoxicity and hemolytic activity, were conducted. In a phase I, double-blind, placebo-controlled clinical trial, healthy adults were randomized into H. coagulans AO1167B and placebo groups for 60 days. Daily capsule consumption was monitored through clinical and hematological evaluations, adverse event tracking, and health surveys. (3) Results: The genome of H. coagulans AO1167B revealed no concerning features. Disk diffusion tests showed no antimicrobial resistance. The strain exhibited no cytotoxic or hemolytic activity, indicating in vitro safety. No significant differences in clinical or hematological parameters were observed between groups. The most common adverse event, gas, diminished over time. (4) Conclusions: H. coagulans AO1167B demonstrates a suitable safety profile, genetic stability, and probiotic potential for gastrointestinal health, justifying further clinical research.